2011
DOI: 10.5657/fas.2011.0399
|View full text |Cite
|
Sign up to set email alerts
|

A New Record of Pandalid Shrimp Procletes levicarina (Crustacea: Decapoda: Caridea) from Korean Waters

Abstract: The pandalid shrimp Procletes levicarina (Bate, 1888) was newly collected from the western and southern waters of Jeju Island, Korea. This species is the only known member of the genus Procletes which belongs to the family Pandalidae. Morphological description and illustration with a color photograph of the species are given. With the addition of P. levicarina, the family Pandalidae in Korean waters consists of 10 species belonging to 5 genera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…In India the species is reported only from Andhra Pradesh, Bay of Bengal (Lalitha, 1980;Shanis, Akhilesh, Manjebrayakath, Ganga, & Pillai, 2012) and now from Gujarat. Remarks: The specimens agree well with the description and illustration provided by Chace (1985) and Kim et al (2011). The specimen examined in the present study bears six spines on merus of fifth pereiopod whereas the Korean specimens examined by Kim et al (2011) have seven-eight spines.…”
Section: Distributionsupporting
confidence: 87%
See 4 more Smart Citations
“…In India the species is reported only from Andhra Pradesh, Bay of Bengal (Lalitha, 1980;Shanis, Akhilesh, Manjebrayakath, Ganga, & Pillai, 2012) and now from Gujarat. Remarks: The specimens agree well with the description and illustration provided by Chace (1985) and Kim et al (2011). The specimen examined in the present study bears six spines on merus of fifth pereiopod whereas the Korean specimens examined by Kim et al (2011) have seven-eight spines.…”
Section: Distributionsupporting
confidence: 87%
“…Remarks: The specimens agree well with the description and illustration provided by Chace (1985) and Kim et al (2011). The specimen examined in the present study bears six spines on merus of fifth pereiopod whereas the Korean specimens examined by Kim et al (2011) have seven-eight spines. The color pattern of specimens examined in the present study also showed similarity with Lalitha (1980) and Kim et al (2011).…”
Section: Distributionsupporting
confidence: 87%
See 3 more Smart Citations